2023
DOI: 10.1109/access.2022.3233870
|View full text |Cite
|
Sign up to set email alerts
|

Design of a Dual-Permanent-Magnet Vernier Machine to Replace Conventional Surface-Mounted Permanent Magnet Motor for Direct-Drive Industrial Turbine Application

Abstract: Surface-mounted permanent magnet motors (SMPMMs) have been widely used in industrial fields. However, when it comes to direct-drive low-speed large-torque fields, SMPMMs have several problems, such as lower slot filling factor, complicated fabrication, low efficiency, and bulky size. Recently, dual-permanent-magnet Vernier motors (DPMVMs) have been investigated due to their high torque density for low-speed direct-drive applications. However, so far, there is little research that demonstrates the application o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The finite element method (FEM) is frequently used to analyze complex motor structures, as it has been demonstrated that the simulation results obtained by using FEM are highly consistent with experimental results, indicating the accuracy and reliability of FEM analysis [23][24][25].…”
Section: Introductionmentioning
confidence: 79%
“…The finite element method (FEM) is frequently used to analyze complex motor structures, as it has been demonstrated that the simulation results obtained by using FEM are highly consistent with experimental results, indicating the accuracy and reliability of FEM analysis [23][24][25].…”
Section: Introductionmentioning
confidence: 79%
“…Permanent magnet machines (PMM) can be used as power-generating or power-driven machines, which adopt permanent magnet (PM) instead of excitation winding. Vernier PMM (VPMM) [1]- [3] possesses vernier modulation effect. In recent years, VPMMs have received wide attention due to their simple constructions and high torque densities.…”
Section: Introductionmentioning
confidence: 99%
“…In general, researchers aim to reduce magnet volume and increase the amplitude of air-gap flux density [23]. To achieve these goals, Halbach-array magnets placed in the slot opening have been introduced in DAG-PMSMs, resulting in a 43% improvement in torque density compared to conventional single air-gap PMSMs [24,25]. Other topologies for DAG-PMSMs have also been proposed to achieve high torque density compared to single air-gap machines [26][27][28].…”
Section: Introductionmentioning
confidence: 99%